Pengaruh Metode Penyeduhan dan Penambahan Jenis Ekstrak Jeruk terhadap Karakteristik Seduhan Kopi Liberika Honey Process - Rizki Galeh Prayoga; Dina Mardhatilah; Adi Ruswanto (Program Studi Teknologi Hasil Pertanian, 2026)
This study aimed to evaluate the characteristics of Liberica honey coffee enriched with different citrus extracts (lemon, Sunkist orange, and lime) prepared using three brewing methods, namely French press, V60, and cold brew, as well as to assess panelists' preferences for the resulting beverages. A two-factor Randomized Complete Block Design (RCBD) was employed with two replications. Factor A consisted of brewing methods (French press, V60, and cold brew), while Factor B comprised the addition of citrus extracts (lime, Sunkist orange, and lemon). The evaluated parameters included pH, vitamin C content, total color difference, caffeine content, and sensory attributes (color, taste, and aroma). The results indicated that the combination of the cold brew method and lemon extract (A3B3) achieved the highest overall preference score from the panelists, with a mean value of 5.48..